The design of coupled microstrip lines - 265507 Akhtarzad, Sina; Rowbotham, Thomas R.; Johns, Peter B.
Although graphical results and formulas are available for the design of microstrip couplers, the design procedure is hampered because even- and odd-modeimpedances are always expressed in terms of the physical geometry. In practice the designer obtains these impedances and then requires to know the geometry given by them. A new design procedure for coupled parallel microstrip lines is therefore presented. The techniques enables the geometry of the coupled lines to be obtained directly from the required even- and odd-mode impedences and uses single microstrip-line geometry as an intermediate step. The results are presented in graphical form using only two universal families of curves. Results are also presented in the form of simple formulas for designprograms and also comparisons with practical results are made.